2017
DOI: 10.1073/pnas.1705181114
|View full text |Cite
|
Sign up to set email alerts
|

Arresting dissolution by interfacial rheology design

Abstract: A strategy to halt dissolution of particle-coated air bubbles in water based on interfacial rheology design is presented. Whereas previously a dense monolayer was believed to be required for such an "armored bubble" to resist dissolution, in fact engineering a 2D yield stress interface suffices to achieve such performance at submonolayer particle coverages. We use a suite of interfacial rheology techniques to characterize spherical and ellipsoidal particles at an air-water interface as a function of surface co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 37 publications
5
95
0
Order By: Relevance
“…In general, β is in the range 2–8, and η is typically 0.2–0.4. Similar behavior was seen by Beltramo et al and Cicuta et al for micrometer‐sized particles, while Maestro et al observed similar values for Gnormals for silica NPs. In all cases Gnormals is between 0.1 and 1 N m −1 , even though the particle size ranged from 14 nm up to 3 µm.…”
Section: Quantitative Descriptions Of Complex Interfacessupporting
confidence: 85%
See 2 more Smart Citations
“…In general, β is in the range 2–8, and η is typically 0.2–0.4. Similar behavior was seen by Beltramo et al and Cicuta et al for micrometer‐sized particles, while Maestro et al observed similar values for Gnormals for silica NPs. In all cases Gnormals is between 0.1 and 1 N m −1 , even though the particle size ranged from 14 nm up to 3 µm.…”
Section: Quantitative Descriptions Of Complex Interfacessupporting
confidence: 85%
“…For the case of liquid–fluid interfaces and interfaces wetted by reversibly adsorbed components, Γ ij = 0 and the surface stress is exactly equal to the liquid–fluid surface tension as measured using pendant drop or Wilhelmy plate. In the presence of material that is quasi‐irreversibly bound to the liquid–liquid interface Γ ij becomes significant, and gives rise to the complex shapes observed in Pickering emulsions, liquid capsules, bijels, and, most recently, printed and molded liquids …”
Section: Quantitative Descriptions Of Complex Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of an oleofoam is influenced by several factors. Crystals can adsorb at the air-oil interfaces of the bubbles (Mishima et al 2016;Heymans et al 2017) and impart interfacial elasticity, similar to that observed for aqueous Pickering foams (Basheva et al 2011;Beltramo et al 2017;Binks 2002;Hunter et al 2008;Stocco et al 2011), therefore preventing bubble dissolution. Another contributing factor is the rheology of the bulk oleogel formed by the crystals remaining in the oil phase.…”
Section: Introductionmentioning
confidence: 67%
“…The particle-stabilising effect is generally attributed to a kinetic barrier (pictured as an 'armored' bubble or droplet) formed by the adsorbed particles, thereby preventing coalescence of droplets [6], although for very specific systems, a thermodynamically stable Pickering emulsion has been achieved [7]. 10 However, it now seems that a sufficient condition for droplet stabilisation is a yield stress interface, which can even be achieved with sub-monolayer coverage [8,9,10]. Here the surface structure must play an important role in determining the mechanical behaviour of the interface.…”
Section: Introductionmentioning
confidence: 99%